Analisis Bifurkasi Persamaan Longitudinal pada Gerak Roket Tiga Dimensi Tipe RKX-Lapan - Ndaru Atmi Purnami (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
This article discusses about longitudinal equation for the three dimensional rocket motion of RKX-Lapan. The RKX-Lapan’s rocket is guided rocket which was designed using two phases, boosting and sustaining. The rocket has six degrees of freedom movement. The freedom movements consists of three translational motions and three rotational motions which causess unstable rocket movement. Therefore, stable rocket motion system is needed. The rocket motion system is three dimensional of nonlinear equation, thus linearization process of rocket motion equation is requaired. One of this linearization process is longitudinal motion which consists of two translational motions and one rotational motion. The equation of longitudinal motion has stabilization system analysist on sustaining phase. Bifurcation analysis of longitudinal equation for the three dimensional rocket motion of RKX-Lapan has been created in this article. It determined equilibria and its equation stability character. Furthermore, bifurcation analysist on equilibria and numerical simulation have been done to find out that bifurcation value indicated a topologically nonequivalent.